How can parallel algorithms help to find new sequential algorithms? - Nagy, Zoltan M (Journal of chemical information and computer sciences, 1993)
Paper presented at the American Chemical Society Symposium on Modern Methods of Substructure Searching, Washington, DC, Aug 92. Describes a logical computing model, based on the relaxation method, for chemical substructure searching. A combination of ring perception and labelling is used to create algorithms for checking isomorphism of molecules and substructure searching. Original abstract-amended.